Adaptación de un sistema de enfriamiento para la condensación de gas de pirólisis de llantas usadas a nivel de laboratorio (2023)
The purpose of this project is to develop the adaptation, redesign and reconditioning of a cooling system that was in the facilities of the Universidad de América, from a degree project in 2002, which had already completed its useful life. and for some years it was out of use and ready to be discarded and used as scrap. Due to the environmental and circular economy focus of the project addressed throughout this document, it was determined that it is appropriate to allocate part of this cooling system, specifically the heat exchanger so that it is capable of cooling and condensing the product gas. of the pyrolysis of used tires, for this, different bibliographic resources were used that allowed the analysis of design and construction criteria, with considerations that allow understanding and deepening the basic engineering behind these processes, and also understanding and addressing environmental problems such as End-of-life tires that are not reused and are not disposed of responsibly.